Safety and tolerability of atomoxetine hydrochloride in a long-term, placebo-controlled randomized withdrawal study in European and non-European adults with attention-deficit/hyperactivity disorder - Camporeale, Angelo; Upadhyaya, Himanshu; Ramos-Quiroga, J. Antoni; Williams, David; Tanaka, Yoko; Lane, Jeannine R.; Escobar, Rodrigo; Trzepacz, Paula; Allen, Albert J (The European journal of psychiatry, 2013)
Background and Objectives: Safety and tolerability of atomoxetine were studied in the largest double-blind, placebo-controlled, randomised withdrawal trial of atomoxetine (80 or 100 mg/day) in adults with attention-deficit/hyperactivity disorder (ADHD). Methods: Patients (N = 2017), 18 to 50 years of age, with ADHD were enrolled from 18 countries. Patients who responded to atomoxetine during a 12-week open-label treatment phase and maintained that response during a 12-week double-blind maintenance phase were randomised to atomoxetine (N = 266) or placebo (N = 258) for 25 weeks of double-blind treatment. Treatment differences were compared for serious adverse events (AEs), treatment-emergent AEs (TEAEs), discontinuation due to AEs, vital signs, body weight, and electrocardiograms. Adapted from the source document.